Management of Infective Endocarditis in Infarction Stroke - Indra Pratama; Gebby Puspita (Newinera Publisher, 2025)
Infective endocarditis (IE) is an infection of the endocardial surface of the heart often involving the heart valves characterized by the formation of vegetations composed of bacteria, fibrin, and platelets. The incidence of IE in high-income countries is estimated at 3–10 per 100,000 person-years, with regional variations; this rate remains relatively stable, but the complexity of cases and neurological complications remain a major concern. Two authors conducted a comprehensive literature search of PubMed, Scopus, NCBI, and Cochrane CENTRAL databases from 2024 to July 2025. Studies were reviewed based on incidence of infective endocarditis in infarction stroke. Infective endocarditis remains an important cause of ischemic stroke, primarily through septic emboli originating from vegetations on the heart valves. Key risk factors include the size and mobility of the vegetation, left valve involvement (mitral or aortic), and virulent pathogens such as Staphylococcus aureus. Clinical vigilance, timely antimicrobial therapy, and careful timing of surgery are key to successful management of ischemic stroke due to IE